A Preliminary Study on the Long-Term Structural Stability of Ventilation Ducts in Cold Regions - Xuejun Chen; Lei Wang; Zhikui Liu; Yinghong Qin (Civil Engineering Journal, 2019)
The construction of roadways in permafrost regions modifies ground-surface conditions and consequently, negatively varies thermal stability of the underlying frozen soils. To avoid the thawing of the permafrost layer under the scenario of global warming, roadways are usually laid on a built-up embankment, which not only disperses the traffic loads to underlying layers but also minimize the thermal disturbance. In the embankment, duct ventilation, or called air duct, can be embedded to further cool the underlying permafrost. While the thermal performance of duct ventilations has been well documented, the long-term structural stability of duct ventilation remains unknown. This study examines the structural stress of ventilation ducts that are placed in harsh weather such as the Qinghai-Tibet Plateau. The ducts are currently buried in the embankment filler, with the wind-outlet and -inlet ends exposed and cantilevered out of the embankment. Field studies found that the exposed parts have plagued cracking and even failures, especially at the fixed end of the cantilevered part. Damages of these concrete ducts are attributed to cyclic freezing-thawing attack, thermally-induced stresses, moisture-induced stresses, and concrete swelling. These physical attacks are caused by the harsh weather in the Qinghai-Tibet plateau. It is recommended to insulate the exposed part of the ducts and to fabricate durable and dense concrete ducts.